Features of correction of vitamin D deficiency in patients with diabetic kidney disease: the role of vitamin D-binding protein - V.M. Yerokhovych; O.V. Karpenko; Ye.I. Ilkiv; N.M. Kobyliak; I.A. Paliienko; I.V. Krasiuk; Iu.I. Komisarenko (Počki)
Background. The relevance of the problem of kidney damage in diabetes mellitus (DM) lies in the annual progressive growth in the number of affected people. Bone mineral disorders occur with high frequency in such patients and require early diagnosis and timely correction. Vitamin D metabolism depends on some factors, including the level of blood transport proteins, such as vitamin D-binding protein (VDBP). Recently, increasing attention has been paid to the role of VDBP among the causes of bone mineral disorders and their pathogenetic relationship with kidney damage in people with type 2 DM. The purpose of the work is to assess the features of phosphorus-calcium metabolism in patients with diabetic kidney disease and the role of VDBP level in the correction of vitamin D deficiency. Materials and methods. In the first stage of the study, 84 people with type 2 DM and chronic kidney disease stages I–III participated, they were divided into 3 groups according to the estimated glomerular filtration rate (eGFR), and underwent assessment of baseline indicators of phosphorus-calcium metabolism. In the second stage, the results of the vitamin D deficiency correction were evaluated in 32 people during dynamic observation after taking cholecalciferol for 3 months. Results. The median vitamin D (25OH) values corresponded to the level of deficiency regardless of the eGFR, with the lowest value in group 3 — 13 (8.48–16.4) ng/ml, which differed from the median indicators of groups 1 (16.38 (13.88–19.83) ng/ml) and 2 (18 (12.8–20.74) ng/ml), p < 0.05. Analysis of the serum VDBP depended on eGFR: the lowest level was observed in group 1 — 93.6 (68.17–109.67) ng/ml and increased in accordance with a decrease in eGFR: 101.07 (75.34–132.84) ng/ml in group 2, 132.82 (97.3–168.8) ng/ml in group 3, with significant difference between groups 1 and 2 (p < 0.01). The effectiveness of the vitamin D deficiency correction appeared to be better in patients with lower blood level of VDBP. Thus, it was significantly higher in the subgroup of patients who did not reach the optimal content of vitamin D (25(OH)D) after 3 months (31 %) compared to those who reached 25(OH)D ≥ 30 ng/ml. Conclusions. VDBP is an important factor in the processes of vitamin D metabolism, its level should be taken into account when correcting bone and mineral disorders in patients with diabetic kidney disease. The study showed that there is an increase in the serum VDBP with the progression of chronic kidney disease on the background of type 2 DM. The effectiveness of treatment depends on the blood level of VDBP in such patients. In case of serum VDBP increase, the effectiveness of treatment is lower, probably due to reduced bioavailability of free vitamin D and its active conversion since active 1,25(OH)2D binds more strongly to VDBP.